2012
DOI: 10.4149/neo_2012_052
|View full text |Cite
|
Sign up to set email alerts
|

Biologic importance and prognostic significance of selected clinicopathological parameters in patients with oral and oropharyngeal squamous cell carcinoma, with emphasis on smoking, protein p16INK4a expression, and HPV status

Abstract: The aim of this study is to evaluate the biologic importance and prognostic significance of selected clinicopathological parameters in patients with oral (OSCC) and oropharyngeal (OPSCC) squamous cell carcinoma, with emphasis on smoking, protein p16INK4a (p16) expression, and human papillomavirus (HPV) status. The study sample consisted of 48 patients with OSCC and 44 patients with OPSCC. Half of the patients were nonsmokers and the other half were gender-, age-and tumor localization-matched smokers.p16 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 44 publications
4
18
0
Order By: Relevance
“…HR-HPV is an important risk factor for a subset of head and neck cancer, particularly in oropharyngeal SCC with highly variable detection rates, reaching up to 80 % [12,13,39,40]. HPV-positive oropharyngeal SCC usually affects slightly younger patients, nonsmokers or light smokers, nondrinkers, patients with good oral hygiene, and probably higher (oral) sexual exposure [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HR-HPV is an important risk factor for a subset of head and neck cancer, particularly in oropharyngeal SCC with highly variable detection rates, reaching up to 80 % [12,13,39,40]. HPV-positive oropharyngeal SCC usually affects slightly younger patients, nonsmokers or light smokers, nondrinkers, patients with good oral hygiene, and probably higher (oral) sexual exposure [11].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the latter, oropharyngeal SCC, affecting mostly the palatine tonsils and root of the tongue, shows the strongest, although highly variable association with HR-HPV infection [11][12][13]. In sinonasal carcinoma, HPV detection rates vary significantly from 0 to 100 % [2,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29] have identified a high proportion of OCSCC with detectable HPV DNA (Table 1). In a recent systematic review, summarizing 60 publications on 4195 patients with OCSCC, Isayeva et al [30] found that 705 (16.8%) of these tumors contained HPV DNA especially the HPV16 genotype.…”
Section: Oral Cavity Squamous Cell Carcinoma and Hr-hpv Infectionmentioning
confidence: 98%
“…Basaloid differentiation is anecdotally noted by some pathologists to be associated with p16 positivity. This association, however, has not been adequately quantified in the literature [3,11,12,15], nor has the prognostic implications of basaloid differentiation been described.…”
Section: Introductionmentioning
confidence: 99%